New records of the damsel bug Alloeorhynchus reinhardi Kerzhner & Günther, 1999 (Hemiptera, Heteroptera, Nabidae) from Japan - Jun Souma; Tatsuya Nozaki; Keiichi Otsui; Tadashi Ishikawa (Check List, 2022)
To date, the damsel bug Alloeorhynchus reinhardi Kerzhner & Günther, 1999 (Hemiptera, Heteroptera, Nabidae, Prostemmatinae, Prostemmatini) has been reported from China and Korea. We report from Japan for the first time A. reinhardi, which represents the second member of the genus in the country. This species inhabits the ground surface of grasslands in Kyushu.